Isolasi Dan Karakterisasi Lipase Dari Rebung Bambu Betung Dendrocalamusasper - Agung Prasetyo; Winni Astuti; Chairul Saleh (JURNAL KIMIA MULAWARMAN, 2017)
This research was conducted to get the extract of rough lipase produced by bamboo shoots (Dendrocalamus asper). Lipase isolation from bamboo shoots was done by blending bamboo shoots to produce the crude extract of the enzyme. Lipase crude extracts that occurred at centrifugation at 12000 rpm for 30 minutes at 4°C. The crude extracts obtained were then tested using quantitative pH 7, temperature 30ºC and substrate 1% (v/v). Based on research there is activity of crude extract of lipase equal to 2,24 U/ml.